390 A RARE CAUSE OF POLYURIA. Issue 1 (1st January 2007) - Wolf, F.; Cook, D.
Abstract : Case History: A 36-year-old female presents with a lifelong history of polydipsia and polyuria of 4 to 8 L/day. She is on no medications. Her father and two paternal uncles have the same symptoms. Evaluation: She has no electrolyte or glucose abnormalities; her serum sodium is 141. Maximum urine osmolality after water deprivation is 36 mOsm/kg and does not respond to exogenous vasopressin (DDAVP). Antidiuretic hormone (ADH) level during the test is 10.2 pg/mL (normal < 4.8). Because her family history is suggestive of an autosomal dominant (AD) disorder, genetic studies are done and reveal an E258K mutation of the aquaporin 2 (AQP2) gene. Discussion: Less than 1% of patients (only seven families) diagnosed with familial nephrogenic diabetes insipidus (NDI) have mutations in the AQP2 gene on chromosome 12q13 that are inherited in an AD fashion. AQPs are expressed as homotetramers; however, monomers are functional. When expressed in oocytes, AQP2 mutants form heterotetramers with wt-AQP2, which are missorted and retained in the Golgi apparatus and other organelles. In comparison, autosomal recessive (AR) mutations of AQP2, which comprise 9% of all NDI, lead to misfolding and trapping of the mutants in the endoplasmic reticulum and a more severe phenotype. This includes an earlier presentation of symptoms and a complete lack of response to DDAVP with urine concentrating ability less than 200 mosmol/kgH2 O when compared to AD AQP2 mutations. Mutations of the vasopressin type 2 receptor (V2R) are the most common cause of familial NDI, responsible for over 90% of cases. These loss-of-function mutations are inherited in an X-linked recessive manner. The severity of the phenotype is variable, depends on which step in the processing of V2R is affected, and may be partially responsive to DDAVP. Conclusion: Several genetic etiologies for NDI are now known. A detailed family history is important to identify potential inherited disorders. Careful characterization of the NDI phenotype can help guide genetic testing; however, there is some degree of overlap in the genotype-phenotype correlation.